Answer:
(0, 0) is the solution of the inequality y - 9 > 3x - 10.
Explanation:
Given the solution point
Let us substitute the point (0, 0) in the inequality to determine which inequality satisfies the equation or not.
CHECKING FOR
y - 9 > 3x + 10
substiture (0, 0) i.e. x = 0, y = 0 in the inequality
0 - 9 > 3(0) + 10
-9 > 10
FALSE
CHECKING FOR
y - 9 > 3x - 10
substiture (0, 0) i.e. x = 0, y = 0 in the inequality
0 - 9 > 3(0) - 10
-9 > 10
True
CHECKING FOR
y + 9 > 3x + 10
substiture (0, 0) i.e. x = 0, y = 0 in the inequality
0 + 9 > 3(0) + 10
9 > 10
FALSE
Therefore, we conclude that only the second inequality i.e. y - 9 > 3x - 10 satisfies the inequality.
Hence, (0, 0) is the solution of the inequality y - 9 > 3x - 10.